(untitled) (Education in the 21st Century, 2023)
The article substantiates the role of a teacher of an institution of higher education in relation to effective training of future specialists. Emphasis is placed on the need for quality preparation of degree students for pedagogical activities, as it depends on the formation of future professionals in the necessary professional competencies and professionalism. An example of such training at the third (educational and scientific) level at the Kherson State Agrarien and Economic University is given. It is noted that together with traditional pedagogical competencies (methods, forms, teaching aids, etc.) future teachers should develop competencies in the use of innovative pedagogical technologies. These are the platforms that are recommended to future doctors of philosophy for use during the educational process in distance mode, in particular: Moоdle, Google Meet, Google Class, Zoom ets. Their positive advantages and necessity of application are substantiated.